2009
DOI: 10.1111/j.1468-1331.2009.02764.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of F‐waves in patients with unilateral lumbosacral radiculopathy

Abstract: Our results show that the use of F-waves may improve the electrodiagnosis of the ULSR if the number of repeater waves is evaluated given the clear and consistent increase of this variable in patients with lumbosacral root injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…The comparison between patient groups in all three nerves did not point to an association of increased total Freps with any particular pathological condition among those studied here. Irrespective of the absolute numbers of repeater F‐waves, the mean difference between healthy controls and patients with CTS, ALS, or L5 root lesion found in this study were proportionally similar to those previously reported 2–5. Repeater F‐waves have not been systematically assessed in polyneuropathies; only one report described 3 patients with diabetic polyneuropathy and showed an increased frequency of RNs 12…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The comparison between patient groups in all three nerves did not point to an association of increased total Freps with any particular pathological condition among those studied here. Irrespective of the absolute numbers of repeater F‐waves, the mean difference between healthy controls and patients with CTS, ALS, or L5 root lesion found in this study were proportionally similar to those previously reported 2–5. Repeater F‐waves have not been systematically assessed in polyneuropathies; only one report described 3 patients with diabetic polyneuropathy and showed an increased frequency of RNs 12…”
Section: Discussionsupporting
confidence: 86%
“…For the ulnar nerve, using 100 stimuli in 11 healthy volunteers, Guiloff and Modarres‐Sadeghi11 reported a mean value of index RN of 11.2 ± 4.9, which was reduced to 5.7 ± 6.0 when samples of 20 stimuli were assessed; similarly, using 200 stimuli in 21 subjects, Peioglou‐Harmoussi et al3 estimated the median value of RN to be 3.3 (min–max: 1.1–5.4), as compared with our median value of RN of 0 (5th–95th percentile: 0–2.4). Pastore‐Olmedo et al5 found a mean value of persistence of total Freps of 18.6 ± 15.7 in the fibular nerve of 5 healthy subjects using 30 stimuli, as compared with our median value of 0 (5th–95th percentile: 0–22). These comparisons should be interpreted with caution due to the different statistical variables employed in different studies.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Studies have shown a wide range of sensitivities (18–74%), depending on the nerve root involved, the F‐wave parameter analyzed, and reference values used . Various F‐wave parameters have been studied, including minimum, maximum, and mean latency, as well as persistence, chronodispersion, duration, and number of repeater F‐waves . Although each of these parameters can provide meaningful information regarding conduction in proximal axons, the minimum reproducible latency compared with an absolute reference value is the measurement that is recorded most efficiently and reported most widely in clinical practice.…”
Section: Discussionmentioning
confidence: 99%